The evolution of custom microarray manufacture. - Garner, H.R.
Given the enormous size of the genome and that there are potentially many other types of measurements we need to do to understand it, it has become necessary to pick and choose one's targets to measure because it is still impossible to evaluate the entire genome all at once. What has emerged is a need to have rapidly customizable microarrays. There are two dominant methods to accomplish custom microarray synthesis, Affymetrix-like microarrays manufactured using light projection rather than semiconductor-like masks used by Affymetrix to mass manufacture their GeneChipTM arrays now, or the ink-jet printing method employed by Agilent. The manufacture of these custom Affymetrix-like microarrays can now be done on a digital optical chemistry (DOC) machine developed at the University of Texas Southwestern Medical Center, and this method offers much higher feature numbers and feature density than is possible with ink-jet printed arrays. On a microarray, each feature contains a single genetic measurement. The initial DOC prototype has been described in several publications, but that has now led to a second-generation machine. This machine reliably produces a number of arrays daily, has been deployed against a number of biomedical questions, is being used in new ways and has also led to a number of spin-off technologies.
Keywords: Affymetrix-like microarrays; University of Texas Southwestern Medical Center; Biomedical questions; Custom microarray manufacture evolution; Digital optical chemistry machine; Ink-jet printed arrays; Light projection; Rapidly customizable microarrays; Semiconductor-like masks; Single genetic measurement; Spin-off technologies; GeneChipTM arrays